The Ordeal of the Reunion : A New History of Reconstruction - Summers, Mark W. (Mark Wahlgren), 1951- (Book collections on Project MUSE., 2014)
For the past several decades, scholarship on the Reconstruction era has placed the struggles of the recently enslaved for a meaningful freedom at the centre of discussions about the period's policies, successes, and failures. But this book synthesises and reorients the existing scholarship to focus on the loyal citizenry that imposed Reconstruction and the defeated Confederates who had to come to terms with it.